E3 ubiquitin ligase RNF10 promotes dissociation of stalled ribosomes and responds to ribosomal subunit imbalance - Lehmann, Janina A.; Lindner, Doris; Sung, Hsu-Min; Stoecklin, Georg (Nature Communications, 2024)
Perturbation of protein synthesis causes ribosome stalling on mRNAs. Here, Lehmann et al. demonstrate that the E3 ubiquitin ligase RNF10, through monoubiquitination of RPS3, promotes dissociation of the small ribosomal subunit upon ribosome stalling.